Study on the laser-induced damage of thin films by terahertz time-domain spectroscopy - Shang, Xiaoyan; Shi, Wei; Su, Junhong; Dong, Chengang (Frontiers in Physics, 2022)
the undamaged and damaged areas of ITO thin film deposited on silicon substrate induced by laser with different energies were tested with the transmission terahertz time-domain spectroscopy system. Their time-domain spectra and frequency domain spectra of 0.4 1.0THz were obtained, the differences were analyzed between the undamaged and damaged areas in these two spectra. The results show that the peak-to-peak value in time domain and the amplitude in frequency domain of the damaged area obviously increase compared with those of the undamaged area，and with the increase of laser induced energy resulting in the damaged area larger and the surface roughness heavier, these two parameters gradually decrease. For the damaged area of ITO thin film with the undamaged substrate , the refractive index, absorption coefficient are lower than those of the undamaged area. Therefore, the variation in the terahertz time-domain and frequency domain spectra could be utilized to distinguish the damage of optical thin film irradiated by laser, which provides a new approach for the laser induced damage identification and the technical support in effect of the laser induced damage on the properties of the optical thin film element in the terahertz band.